A Strategic Investigation on Diabetic Nephropathy; Its Conceptual Model and clinical Manifestations: A Review - Wal, Pranay; Tyagi, Sachin; Pal, Rashmi S.; Yadav, Anil; Jaiswal, Riya (Current Diabetes Reviews, 2023)
Diabetes is a major health issue, and its complications can lead to various health problems. Nephropathy has been recognised since the 1930s, when Kimmelstiel and Wilson first reported the characteristic nodular glomerulosclerosis lesions in diabetic kidneys. Diabetic nephropathy (DN), commonly known as diabetic kidney disease, is a condition in which people with diabetes have excessive quantities of urine albumin excretion, diabetic glomerular lesions, and a reduction in their glomerular filtration rate (GFR). Type 1 diabetes (autoimmune -cell destruction and absolute insulin insufficiency), type 2 diabetes (relative insulin deficit and resistance), and others are the three forms of diabetes (e.g., pancreatic disease). Diabetes nephropathy is the leading cause of chronic kidney disease and end-stage renal failure worldwide. Much research has been conducted in both basic science and clinical therapies to enhance the understanding of the mechanism of diabetic nephropathy and expand available therapeutics. Diabetic nephropathy prevention continues to rely on screening for microalbuminuria and treating hyperglycemia. However, several studies suggest that managing diabetic kidney disease is more challenging. Despite comparable hyperglycemic management, some studies suggest that the incidence of renal problems varies by patient. As a result, there has been a great deal of interest in studying the inherent renal protective effects of various antihyperglycemic drugs. This study aims to provide information about the diabetic kidney disease conceptual model, pathogenesis, screening, and diagnosis. It will also address the treatment and prevention of diabetic nephropathy, focusing on comparing the mechanisms, safety profiles, and efficacy of different antihyperglycemic medications.
Keywords: Diabetic nephropathy